CORRELATION OF USING INSTAGRAM FOR LEARNING WRITING WITH STUDENTS' WRITING MOTIVATION - Wangsa Kusuma Putra; Rissa San Rizqiya (IKIP Siliwangi, 2023)
The aim of the study examines the relationship of using Instagram with students’ writing motivation. This research is quantitative with the correlation method. The population was students of eighth grade at SMP Negeri 3 Cimahi in the academic year 2020/2021. A total of 76 students took part in the two classes, the sample was 38 students. The instruments used to collect data were a test of writing by using Instagram as a learning medium and questionnaires to determine students' writing skills. The results show a correlation greater than zero points (0.702 > 0); meanwhile, the significant of the correlation is 0.01. Furthermore, the correlation is below 0.05 in the positive direction. It can be implied that the correlation of using Instagram for learning writing with students' writing motivation can be concluded as Significant Positive. To conclude teachers of English writing can use Instagram as a medium to improve students’ motivation to write. Keywords: Instagram; Motivation; Writing